THE THE DEEP TRANSVERSE FRICTION INTERVENTION BETTER THAN THE MASSAGE EFFLEURAGE IN INCREASING THE RANGE OF CERVICAL MOTION DUE TO OF MYOFASCIAL PAIN SYNDROME OF UPPER TRAPEZIUS MUSCLE ON THE LAUNDRY’S WORKERS IN EAST DENPASAR - Aprilia, Komang Putri; Adiputra, I Nyoman; Wahyuni, Nila (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 1 (2018): Majalah Ilmiah Fisioterapi Indonesia, 2018)
THE DEEP TRANSVERSE FRICTION INTERVENTION BETTER THAN THE MASSAGE EFFLEURAGE IN INCREASING THE RANGE OF CERVICAL MOTION DUE TO OF MYOFASCIAL PAIN SYNDROME OF UPPER TRAPEZIUS MUSCLE ON THE LAUNDRY’S WORKERS IN EAST DENPASAR ABSTRACT Range of Motion (ROM) defined as the extent of joint’s movement that occurs when the joint was moved from one position to another, either passively or actively. Bad habits that done by someone if it done repeatedly and for a long time could trigger pain and tension around the neck as well as decrease in the flexibility of the neck muscles. Decrease in muscle flexibility would result in decreased the range of cervical motion that will interfere with a person's daily activities. The purpose of this study was to prove the intervention Deep Transverse Friction better than Massage Effleurage in increasing the range of cervical motion as a result of Myofascial Pain Syndrome in Upper Trapezius muscle. This research was an experimental design with pre and post two group design. These samples included 20 people who were divided into two groups. Group 1 was given Deep Transverse Friction intervention while group 2 was given Effleurage Massage intervention. Measurement range of motion was done by goniometer. This research was an experimental design with pre and post test two group design. The result showed an increase Range of Motion in the intervention Group 1 amounted 4.65 and intervention group 2 amounted 1.35. Paired sample t-test showed a significant result between intervention group 1 and intervention group 2 with p = 0.000. Difference test between group 1 and group 2 using Mann Whitney U-test was obtained p = 0.000. It was concluded that Deep Transverse Friction intervention better than Effleurage Massage in increasing the range of cervical motion. Keywords: Range of cervical motion, Deep Transverse Friction, Massage Effleurage, Goniometer.